A narrative review of veterinary pharmacovigilance situations and prospects in East African countries - Mekasha, Yesuneh Tefera; Nigussie, Sete; Mekonen, Abibo Wondie; Berrie, Kassahun; Mulaw, Asnakew; Feleke, Melaku Getahun (Frontiers in Veterinary Science, 2024)
BackgroundVeterinary pharmaceuticals must be safe and effective for treating and preventing diseases in animal sectors. Strict adherence to regulations at every stage of production, storage, and administration is necessary as the global sector grows in order to lower the possibility of adverse veterinary drug events. Strong pharmacovigilance regulatory systems are critical in monitoring and managing safety concerns related with veterinary pharmaceuticals.ObjectiveThis review aimed to investigate the implementation of veterinary pharmacovigilance, collaborative initiatives, and reporting practices within the veterinary sector across East African countries.MethodsA thorough search was performed using online platforms such as Google Scholar, PubMed, the Web of Sciences, and regulatory Web sites. The search strategies relied heavily on selecting relevant published findings related to veterinary pharmacovigilance status, veterinary adverse drug event reporting practice, and collaborative efforts in veterinary pharmaceutical sectors within the East African landscape. This article search approach confirmed the inclusion state of veterinary pharmacovigilance and associated collaborative initiatives in the region.ResultsIn comparison to more developed regions, the review indicated that the veterinary pharmacovigilance system in East African countries was still in its early state. A strong legislative foundation and a large commitment from the veterinary profession are needed to establish a nationwide veterinary pharmacovigilance system. The review reveals a significant lack of consistency in the infrastructure of veterinary pharmacovigilance among the countries of East Africa. Tanzania, Kenya, and Ethiopia have some institutional processes for veterinary pharmaceutical safety, but they lack thorough documentation, which suggests that this systems still require improvement. The analysis emphasizes how inadequate the reporting systems are for adverse veterinary medication events in the majority of East African nations. Given the challenges East Africa faces, customized strategies are required to guarantee the safety and oversight of veterinary medications and improve veterinary pharmacovigilance. For systems to be more effective, veterinary pharmaceutical legal frameworks must be strengthened and stakeholder collaboration must be improved. Stakeholders include legislators, law enforcement, customs officials, regulatory organizations, scientists, pharmaceutical businesses, veterinarians, farmers, and the general public.ConclusionA multidisciplinary strategy is needed to solve current gaps in veterinary pharmacovigilance and improve overall veterinary drug safety in East Africa. It is feasible to create more reliable methods for tracking and guaranteeing the safety of veterinary medications by combining the efforts of numerous stakeholders, including as legislators, regulatory agencies, veterinary practitioners, and the general public.